Exploring unconscious threat processing using virtual reality - Ventura, Ana Sofia Tavares da Silva Marques (2021)
Emotions have as primary effect the activation of our body to elicite a quick response. Fear responses created mechanisms to avoid or escape threatening stimuli and events. Through natural selection, the individuals with more effective defensive and visual systems in responding and detecting threat, prevailed. This processing advantage is still present in humans as various studies reveal snakes’ advantage in accessing awareness. Continuous Flash Suppression (CFS) technique allows the study of unawareness processing. In this project, we will compare the results of using CFS in a computer monitor or in a virtual reality device, accessing reaction times, heart rate and skin conductance. To the dominant eye will been presented the stimuli (snakes’ or birds’ images) and to the other eye the Mondrian masks. We will manipulate the stimuli position by visions (foveal or peripheral). We expect advantage of snakes’ stimuli over birds’ images, in both devices, and also modulation of the physiological measures upon appearance of the threat eliciting stimuli. We expect, as well, that snakes’ advantage will be independent of the visual field. This project aims to contribute to the study of threat processing in the human being as well as to evaluate the use of virtual reality in experimental psychology and increase the ecological validity of its use in investigation and psychological intervention.